Analisis Faktor-Faktor yang Mempengaruhi Minat Nasabah dalam Menggunakan Mobile Banking di BSI KC Binjai - Dea Puspita; Muhammad Lathief Ilhamy Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify the factors influencing customer interest in using BSI Mobile Banking at KC Binjai, as well as the obstacles encountered. A qualitative research method with in-depth interviews was used to collect data. The results indicate that ease of access, flexibility, and security are the main factors driving interest, accelerated by the COVID-19 pandemic and social recommendations. The main obstacles include distrust of digital security and a lack of digital literacy, especially among elderly customers. Socialization and promotion efforts by the bank have increased trust, but simplification of the registration process and continuous education are needed. This research emphasizes the importance of a comprehensive approach to increasing the adoption of digital services in Islamic banking